Black carbon and other light-absorbing impurities in snow in the Chilean Andes - Rowe, Penny M.; Cordero, Raul R.; Warren, Stephen G.; Stewart, Emily; Doherty, Sarah J.; Pankow, Alec; Schrempf, Michael; Casassa, Gino; Carrasco Cerda, Jorge Fernando; Pizarro, Jaime; MacDonell, Shelley; Damiani, Alessandro; et al. (My University, 2019)
Vertical profiles of black carbon (BC) and other light-absorbing impurities were measured in seasonal snow and permanent snowfields in the Chilean Andes during Austral winters 2015 and 2016, at 22 sites between latitudes 18 degrees S and 41 degrees S. The samples were analyzed for spectrally-resolved visible light absorption. For surface snow, the average mass mixing ratio of BC was 15 ng/g in northern Chile (18-33 degrees S), 28 ng/g near Santiago (a major city near latitude 33 degrees S, where urban pollution plays a significant role), and 13 ng/g in southern Chile (33-41 degrees S). The regional average vertically-integrated loading of BC was 207 mu g/m(2) in the north, 780 mu g/m(2) near Santiago, and 2500 mu g/m(2) in the south, where the snow season was longer and the snow was deeper. For samples collected at locations where there had been no new snowfall for a week or more, the BC concentration in surface snow was high (similar to 10-100 ng/g) and the sub-surface snow was comparatively clean, indicating the dominance of dry deposition of BC. Mean albedo reductions due to light-absorbing impurities were 0.0150, 0.0160, and 0.0077 for snow grain radii of 100 mu m for northern Chile, the region near Santiago, and southern Chile; respective mean radiative forcings for the winter months were 2.8, 1.4, and 0.6 W/m(2). In northern Chile, our measurements indicate that light-absorption by impurities in snow was dominated by dust rather than BC.
Keywords: Albedo (alchemy); Dominance (genetics)